The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1016/j.nicl.2018.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric MRI as a diagnostic biomarker of frontotemporal dementia: A systematic review to determine clinical applicability

Abstract: Frontotemporal dementia (FTD) is difficult to diagnose, due to its heterogeneous nature and overlap in symptoms with primary psychiatric disorders. Brain MRI for atrophy is a key biomarker but lacks sensitivity in the early stage. Morphometric MRI-based measures and machine learning techniques are a promising tool to improve diagnostic accuracy. Our aim was to review the current state of the literature using morphometric MRI to classify FTD and assess its applicability for clinical practice. A search was compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 62 publications
(147 reference statements)
1
29
0
Order By: Relevance
“…MRI allows detection of bvFTD-specific brain atrophy, which includes frontal and anterior temporal volume loss, and shows a good diagnostic accuracy for differentiating FTD from normal subjects and other dementias in clinical practice [38][39][40]. MRI of bvFTD can show severe frontal and anterior temporal atrophy (Figs.…”
Section: Bvftdmentioning
confidence: 99%
“…MRI allows detection of bvFTD-specific brain atrophy, which includes frontal and anterior temporal volume loss, and shows a good diagnostic accuracy for differentiating FTD from normal subjects and other dementias in clinical practice [38][39][40]. MRI of bvFTD can show severe frontal and anterior temporal atrophy (Figs.…”
Section: Bvftdmentioning
confidence: 99%
“…In an effort to address the need for improved diagnostic biomarkers for the behavioural variant frontotemporal dementia (bvFTD), several studies have demonstrated the potential value of morphometric MRI analysis for diagnostic purposes (McCarthy et al., 2018). Here, we performed a deformation-based morphometry (DBM) study of longitudinal MRI changes in bvFTD.…”
Section: Introductionmentioning
confidence: 99%
“…The best AUC was reported by Raamana et al (AUC 0.938, 100% sensitivity and 88% specificity). However, the main limitation of that study is that the bvFTD diagnosis from the validation cohort was based on clinical criteria (39). Contrarily, the bvFTD subjects from our validation cohort are known carriers of a pathogenic mutation and have therefore, definite bvFTD diagnosis.…”
Section: Discussionmentioning
confidence: 99%